Productivity, smart specialisation, and innovation: Empirical findings on EU macro-regions - Mirko Kruse; Cristina Somcutean; Jan Wedemeier (REGION, 2023)
The paper aims to enrich the discussion on the Research and Innovation Strategies for Smart Specialisation (RIS3) and ongoing development of macro-regions in the EU. EU macro-regions are defined as geographical related places that are considered to be socially, economically, and historically linked and, until now, make a blind spot in the discussion on Smart Specialisation and regional innovation. The empirical approach of this paper is to apply a simply pooled OLS-regression with productivity as an independent variable, various exogenous variables on Smart Specialisation, dummies on EU macro-regions, and time-fixed effects within NUTS2 regions between 2014 and 2018. From this, it can be concluded that Smart Specialisation has a significant dependency on productivity. Moreover, it was assumed that regions of a macro-region benefit from each other by co-location. The result is not perfect. This raises questions for the development of EU macro-regions.
Keywords: O; O47; R11; 330; productivity; smart specialisation; innovation; European structural and investment funds; macro-regions